Tren Kontemporer dalam Audit: Harmonisasi Teknologi dan Keberlanjutan dalam Praktek Audit - Rusli, Urisnawati; Muslianti Middin; , Amiruddin; Syamsuddin (Jurnal Penelitian Ekonomi Akuntansi, 2024)
In the modern era, audit practices are increasingly influenced by technological advancements and the need for sustainability. This article explores the harmonization of technology and sustainability in contemporary audit practices. The research methodology involves the analysis of scientific articles selected based on specific criteria, namely articles published within the time frame of 2015-2024 from journals in quartiles (Q1, Q2, Q3, and Q4). Utilizing the Prisma Watase Uake tool, 25 selected articles were identified. Through a Systematic Literature Review (SLR) approach, this research uncovers several technologies used to enhance the efficiency and accuracy of audits. Furthermore, the study highlights the importance of integrating sustainability into audits to assess the social and environmental impacts of companies. The findings indicate that the combination of technology and sustainability not only improves audit quality but also supports corporate social responsibility objectives. This article provides valuable insights for accounting professionals and researchers to understand the challenges and opportunities in the field of auditing in the future. The article has limitations due to the review of only 25 articles using Prisma Watase Uake, which is considered inadequate for a comprehensive understanding. Further research is needed to increase the volume of literature reviewed and to apply different methodologies. A qualitative approach could offer deeper insights into the experiences of audit practitioners in integrating technology and sustainability, as well as the challenges faced in the field.